The Role of Nested Systems in EFL Students' Willingness to Communicate (WTC) and Engagement - Gu, Lingang; Sun, Pingping (Frontiers in Psychology, 2021)
Language learning is a complex process with many intrapersonal and interpersonal processes which are nested within smaller systems, themselves. Willingness to communicate (WTC) and engagement of students are two of the many complicated, multifaceted, and dynamic variables in L2 learning that have mostly been explored via quantitative, correlational, and one-shot methodologies. However, such a research trend provided only a snapshot of variables of second language acquisition (SLA) nature and dynamism. Against this shortcoming, this study aims to present the conceptualizations, applications, and implications of complexity dynamic system theory for investigating L2 earner-psychology variables, especially WTC and engagement. In doing so, the definitions, dimensions, and key properties of the two constructs were explained. In the end, a series of research gaps, implications, and future directions are suggested for future researchers in this territory.